PENGARUH LINGKUNGAN SEKOLAH DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR MATA PELAJARAN IPS SISWA SMPN 4 PEKANBARU - Anputri, Irnanda; Suarman, Suarman; Haryana, Gani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to determine the effect of school environment and learning motivation on learning results social studies subjects junior high school 4 Pekanbaru. This research is quantitative descriptive. The population in this all student class VIII which amounted to 327 student. the sample was obtained by using purposive sampling method as much as 77 respondents. Data analysis method used is multiple linear regression analysis. The result of this research is the school environment have a significant effect on the student's learning result which is obtained tcount 5,526 > ttabel 1,993 and significant value 0,000< 0,05. Learning motivation have a positive and significant impact on student’s learning result outcomes where obtained tcount 6,169 > ttabel 1,993 and significant value 0,000 <0,05. In silmutan there is a positive or significant influence between school environment and learning motivation with learning results outcomes where obtained fcount 46,291 > ftabel 3.120 and significant value 0,000 <0.05. The result of multiple regression research found that the school environment and learning motivation have a significant effect on the students' learning result outcomes of 55.6% and the rest of 44.4% influenced by other factors outside this study.Key Words: School Environment, Learning Motivation and Learning Result